Melatih Cara Berfikir Komputasi Pada Siswa Sekolah Dasar dan Menengah di Kabupaten Garut - Dewi Tresnawati; Detila Rostilawati; Ayu Latifah; Eri Satria; Asri Mulyani; Sri Rahayu; Leni Fitriani; Rinda Cahyana; Shopi Nurhidayanti; Cha Cha Nisya Asyah (Journal of Community Development, 2024)
Technological advances in the 21st century demand Computational Thinking skills that are increasingly important in the digital era. However, the application of Computational Thinking (CT) at the primary and secondary education levels in Garut Regency is still limited. This study aims to improve the understanding of CT among students in elementary schools, junior high schools, and vocational high schools through a training program that includes pre-test, interactive training, and post-test. The training method was designed according to the educational level of the participants, using Bebras questions to train CT skills. The pre-test results showed an average initial score of 47.19, while the post-test results increased by an average of 25.75 points to 72.94. The findings show that the training successfully improved participants' understanding of CT through a structured approach, including introduction of concepts through sample Bebras problems, practice problems, as well as a comprehensive question and answer session.